(untitled) (Hekima Review, 2015)
In a post-exilic situation, the prophet Malachi had to engage in polemics that would reassure the people of Israel that God loved them. The polemics in the oracle, God’s love for Israel and hate of Edom rhetoric found in Malachi 1:1-5, should be interpreted in context. The love of God cannot be confined in a geographical setting. The “damn Edom theology” that is found in Malachi 1:1-15 can lead readers to conclude that God’s love is exclusive. However, a contextual reading and a study of the forms in the oracle reveals God’s universal and unconditional love for the people.